Spatiotemporal Changes Posttreatment in Peripheral Arterial Disease. (3rd December 2015) - Myers, Sara A.; Huben, Neil B.; Yentes, Jennifer M.; McCamley, John D.; Lyden, Elizabeth R.; Pipinos, Iraklis I.; Johanning, Jason M.
Abstract : Accumulating evidence suggests revascularization of peripheral arterial disease (PAD) limbs results in limited improvement in functional gait parameters, suggesting underlying locomotor system pathology. Spatial and temporal (ST) gait parameters are well studied in patients with PAD at baseline and are abnormal when compared to controls. The purpose of this study was to systematically review and critically analyze the available data on ST gait parameters before and after interventions. A full review of literature was conducted and articles were included which examined ST gait parameters before and after intervention (revascularization and exercise). Thirty-three intervention articles were identified based on 154 articles that evaluated ST gait parameters in PAD. Four articles fully assessed ST gait parameters before and after intervention and were included in our analysis. The systematic review of the literature revealed a limited number of studies assessing ST gait parameters. Of those found, results demonstrated the absence of improvement in gait parameters due to either exercise or surgical intervention. Our study demonstrates significant lack of research examining the effectiveness of treatments on ST gait parameters in patients with PAD. Based on the four published articles, ST gait parameters failed to significantly improve in patients with PAD following intervention.